2018
DOI: 10.1051/0004-6361/201832759
|View full text |Cite
|
Sign up to set email alerts
|

Neutral gas properties of Lyman continuum emitting galaxies: Column densities and covering fractions from UV absorption lines

Abstract: Context. The processes allowing the escape of ionizing photons from galaxies into the intergalactic medium are poorly known. Aims. To understand how Lyman continuum (LyC) photons escape galaxies, we constrain the H i covering fractions and column densities using ultraviolet (UV) H i and metal absorption lines of 18 star-forming galaxies that have Lyman series observations. Nine of these galaxies are confirmed LyC emitters Methods. We fit the stellar continuum, dust attenuation, metal, and H i properties to con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
158
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 88 publications
(187 citation statements)
references
References 58 publications
23
158
1
Order By: Relevance
“…We note that the shell-model prediction of the systemic velocity of CR7 presented in Dijkstra et al (2016) agrees perfectly with recent [Cii] measurements in Matthee et al (2017b), suggesting that shell-model fitting is a good tool to recover the systemic redshift of a LAE at high redshift. The column density is also significantly lower than the column density inferred from absorption line measurements in local LyC leakers (Gazagnes et al 2018), which lead these authors to conclude that the Hi covering fraction in these galaxies is non-uniform. A relatively high column density in these local LyC leakers is consistent with their larger Lyα peak separation compared to COLA1, and their typical escape fraction of ≈5%.…”
Section: Lyα Line Properties and Modellingmentioning
confidence: 85%
“…We note that the shell-model prediction of the systemic velocity of CR7 presented in Dijkstra et al (2016) agrees perfectly with recent [Cii] measurements in Matthee et al (2017b), suggesting that shell-model fitting is a good tool to recover the systemic redshift of a LAE at high redshift. The column density is also significantly lower than the column density inferred from absorption line measurements in local LyC leakers (Gazagnes et al 2018), which lead these authors to conclude that the Hi covering fraction in these galaxies is non-uniform. A relatively high column density in these local LyC leakers is consistent with their larger Lyα peak separation compared to COLA1, and their typical escape fraction of ≈5%.…”
Section: Lyα Line Properties and Modellingmentioning
confidence: 85%
“…Moreover, Gazagnes et al (2018) show for galaxies with known Lyman continuum leakage that the escape of ionizing photons is related to the covering factor of the H i gas (rather than low H i column densities). Recent modeling of the Local Group dwarf galaxy IC 10 also shows that on scales of individual star-forming regions, clouds tend to be matter-bounded, allowing for the possibility of photons escaping the regions, while on larger spatial scales, clouds tend to be more radiation-bounded (Polles et al 2019).…”
Section: Phase Filling Factorsmentioning
confidence: 95%
“…In the present work we study eleven z ∼ 0.3−0.4 Lyman continuum emitters discovered with the COS spectrograph on-board HST and whose properties have been amply discussed in several papers (Izotov et al 2016a(Izotov et al ,b, 2018aSchaerer et al 2016Schaerer et al , 2018Verhamme et al 2017;Gazagnes et al 2018;Chisholm et al 2018). The metallicities of these galaxies are in the range 12 + log(O/H) = 7.65−8.16, with a median oxygen abundance of 12 + log(O/H) of 7.91.…”
Section: Optical Emission Line Properties Of Lyc Emittersmentioning
confidence: 99%
“…On the other hand, the detailed analysis of UV absorption lines (including the Lyman series lines of hydrogen and other low-ionization lines) of the z ∼ 0.3−0.4 leakers of Izotov and collaborators undertaken by Gazagnes et al (2018) and Chisholm et al (2018) revealed the presence of high-column-density gas that is optically thick to LyC radiation and co-exists with lines of sight, which allows the escape of UV ionizing and nonionizing radiation from these galaxies. This implies that the ISM of these galaxies cannot be described by simple, one-zone photoionization models, and that a more complex ISM structure should be accounted for to consistently describe these objects.…”
Section: Introductionmentioning
confidence: 99%